Selling rooms online: the use of social media and online travel agents. Issue 2 (4th February 2014) - Inversini, Alessandro; Masiero, Lorenzo
Abstract : Purpose: – This paper aims to focus on the reason why hoteliers choose to be present in online travel agent (OTA) and social media web sites for sales purposes. It also investigates the technological and human factors related to these two practices. Design/methodology/approach: – The research is based on a survey sent to a wide range of hotels in a Swiss touristic region. The empirical analysis involves the specification of two ordered logit models exploring the importance (in terms of online sales) of both social media and the online travel agent, Booking.com . Findings: – Findings highlight the constant tension between visibility and online sales in the web arena, as well as a clear distinction in social media and OTA web site adoption between hospitality structures using online management tools and employing personnel with specific skills. Practical implications: – The research highlights the need for the hospitality industry to maintain an effective presence on social media and OTAs in order to move towards the creation of a new form of social booking technologies to increase their visibility and sales. Originality/value: – This research contributes to understanding the major role played by OTAs and social media in the hospitality industry while underlining the possibility of a major interplay between the two.